AN ANALYSIS OF FIGURATIVE LANGUAGES USED IN WILLIAM SHAKESPEARE'S SONNETS - Yulianda, Nindy; Sunra, La (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
Figurative language is a means of giving words an additional dimension. Poets use figurative language because it allows them to express their ideas more creatively and subtly than if they used direct and flat language. The purpose of this thesis is to identify the many figurative language styles used in the works of William Shakespeare. There are 12 types of figurative language according to Perrine ides. Qualitative descriptive method was used in this study. In this study, sonnets 29, 73, 94, 98, 116, and 131 were sampled. The initial aim of this study was to describe the many figurative language styles used in William Shakespeare's sonnets. Using Perrine theory, the findings of this study indicate that there are nine types of figure of speech found, including simile, metaphor, personification, symbol, synecdoche, hyperbole, paradox, irony, and disparaging. Simile is the most common form of figurative language in selected poems. The second objective of this study is to examine the significance of each figurative phrase used in William Shakespeare's sonnets. The underlying concept, emotion, or mood that poetry expresses is known as meaning. So, the meaning of poetry is the explicit or implied message conveyed by the poet using Leech's theory which divides seven kinds of meaning. Research findings are presented in 25 extracts. Researchers did not find all of them but only found five meanings, namely conceptual meaning, connotative meaning, social meaning, effective meaning, reflection meaning, collotative meaning, and thematic meaning. The most widely used types of meaning are connotative meaning and social meaning.